An Examination of Ethnic Identity, Self-Compassion, and Acculturative Stress in Asian International Students - Tian, Lu; McClain, Shannon; Moore, Marisa M; Lloyd, Howard (Journal of International Students, 2019)
There is a dearth of research examining psychosocial factors that contribute to Asian international students’ acculturative stress. This study examines: (a) whether ethnic identity associates with acculturative stress, (b) whether other-group orientation mediates the relation between ethnic identity and acculturative stress, and (c) whether self-compassion moderates the relation between ethnic identity and acculturative stress. Results indicated that a stronger ethnic identity was associated with heightened acculturative stress. Self-compassion was significantly negatively associated with acculturative stress. Asian international students who strongly affiliated with their own ethnic group reported an increased openness to other ethnic groups and, in turn, reported reduced acculturative stress. Additional studies should examine other mediators that may explain the positive correlation between ethnic identity and acculturative stress.